Variations in postoperative electrolyte concentrations and influential factors in hip arthroscopy - Guanying Gao (BMC Musculoskeletal Disorders, 2022)
Abstract Background Different from arthroscopy in other joints, more perfusion is required for a better access to perform surgical procedures in hip arthroscopic operations. The significant fluid perfused may lead to complications of partial tissue injury and electrolyte imbalance. However, there were few studies on the change of serum electrolyte after hip arthroscopy and the influential factors were still unknown. Methods We evaluated consecutive patients who underwent hip arthroscopy in our hospital between October 2021 and February 2022. Age, sex, and BMI matched patients who underwent arthroscopic anterior cruciate ligament (ACL) reconstruction at the same time were also included as the control group. Preoperative and postoperative serum electrolyte of sodium (Na +), potassium (K +), chloride (Cl-), magnesium (Mg2 +), and carbon dioxide capacity (CO2CP) were analyzed. The correlations between influential factors like perfusion volume, operating time, BMI and hip circumference, and changes in serum electrolyte were also analyzed. Results A total of 79 patients were involved in this study, including 49 patients who underwent hip arthroscopy and 30 patients who underwent knee arthroscopy. For hip arthroscopy, decrease of potassium levels was observed in 40.8% of the patients, and postoperative hypokalemia was found in 10.2% patients. There were significant variations in postoperative sodium, magnesium, chloride and carbon dioxide capacity in hip arthroscopy (p < 0.05). No correlations were found between each of the electrolyte concentrations and influential factors like perfusion volume, operating time, BMI, sex and hip circumference. The significant variations were found in chloride and carbon dioxide capacity in knee arthroscopy (p < 0.05). Conclusions Hip arthroscopy would significantly influence postoperative serum electrolyte, and hypokalemia could be a postoperative complication. The correlation between serum electrolyte and fluid perfusion volume is remained to be investigated. We therefor advocate that performing a systematic care of preoperative and postoperative serum electrolyte analysis as perioperative management is necessary.